Ultrafast Laser‐Induced Metasurfaces for Geometric Phase Manipulation. Issue 1 (7th December 2016) - Drevinskas, Rokas; Beresna, Martynas; Zhang, Jingyu; Kazanskii, Andrey G.; Kazansky, Peter G.
Abstract : Direct‐write femtosecond laser nanostructuring of 300 nanometer thick a‐Si:H films results in space‐variant functional metasurfaces with form birefringence of up to Δ n ≈ –0.5. Engineering the orientation of local optical axis allows implementing continuous phase profiles of nearly any optical element including arrays of polarization microconverters and microlenses, polarization gratings, and computer‐generated holograms with continuous phase gradients of ≈1 rad µm −1 .